Gramsci's Political Thought : An Introduction - Simon, Roger, 1913-2002 (Book collections on Project MUSE., 2015)
Antonio Gramsci was an innovative and wide-ranging thinker whose interpretations of Marxism helped rescue it from determinism and economic reductionism. In the words of Stuart Hall: 'Reading Gramsci has fertilised our political imagination, transformed our way of thinking, our style of thought, our whole political project'. Gramsci's creative use of terms such as hegemony, civil society and historic block adds a new dimension to political vocabulary. But the fragmentary nature of his writings, especially in the Prison Notebooks, means that it is not always easy to grasp the full significance of his ideas. This book, completely revised in 1991 and further revised in 2015, provides an account of Gramsci's work which makes his writing accessible and comprehensible for the contemporary reader.